2005
DOI: 10.5005/jcdp-6-1-123
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Tongue: Clinical Characteristics of 188 Cases

Abstract: The purpose of this study was to investigate the clinical characteristics and assess other factors associated with geographic tongue in Thailand. One hundred and eighty-eight Thais with geographic tongue and 188 controls were interviewed regarding their medical history, symptoms, and the nature and migratory pattern of their lesions. Variations in the clinical appearance, lesion location, and any associated tongue fissures were recorded. The age range for the 188 subjects was 9 to 79 years. The highest inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
3
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 39 publications
10
79
3
9
Order By: Relevance
“…Patients may report of oral discomfort such as burning, pain, excessive salivation and unpleasant taste 1 5. The patient was asymptomatic a year earlier to recovery, which was a similar finding with other studies 4 5. Then he developed pain which was also noticed by Sigal and Mock1 in two children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Patients may report of oral discomfort such as burning, pain, excessive salivation and unpleasant taste 1 5. The patient was asymptomatic a year earlier to recovery, which was a similar finding with other studies 4 5. Then he developed pain which was also noticed by Sigal and Mock1 in two children.…”
Section: Discussionsupporting
confidence: 91%
“…Very few cases have been reported in children4 5 and we found this condition in a 6-year-old child with a history of the lesion since first year of age. Patients may report of oral discomfort such as burning, pain, excessive salivation and unpleasant taste 1 5.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The mean age for the experimental and control group was 12.1 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years. All participants in the case group exhibited lesions 7 6 Maximum 12 12 Percentile 10th 8 9 25th 9 10 50th 12 11 75th 12 12 90th 12 12 Mann-Whitney U test: statistical difference (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated that BMG is more prevalent in young individuals [5,[13][14][15]. However, other authors believe that most of the cases is noted in individuals over 40 years of age [16,17]. BMG is by far the most frequent tongue disease reported in the different studies reviewed on the pediatric population.…”
Section: Introductionmentioning
confidence: 96%